GranDIHC-BR 2025-2035 - GC1: New Theoretical and Methodological Approaches in HCI - da Silva Junior, Deógenes P.; Alves, Daniel Domingos; Carneiro, Nayana; Matos, Ecivaldo de Souza; Baranauskas, M. Cecília C.; Mendoza, Yusseli Lizeth Méndez (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
This Grand Challenge highlights that the HCI field is going through a time when it needs to revisit and find new theoretical and methodological foundations to account for the phenomena it encompasses. Thus, it addresses philosophical aspects of the field, encompasses studies that aim to inform and enrich the understanding of human-computer interaction, and highlights the need to bring, experiment with, and conceive new ways of understanding HCI and acting in it. In addition to the application of multidisciplinary theories from anthropology, linguistics, psychology, design, sociology, and other areas, this Grand Challenge exposes the need to investigate other philosophical positions that have been little explored until now, such as those of a phenomenological nature, the creation of theoretical models, the application of existing theories in new ways, or the synthesis of several theories from a new perspective aiming to describe, explain, or inform the field. Consequently, it includes new methods and techniques for data collection and analysis, design approaches, or evaluation strategies that can be applied to HCI research and practice. This article is presented bilingually in English and Portuguese.